THE NEUROPSYCHOLOGICAL REPERCUSSIONS OF CELIAC DISEASE IN CHILDHOOD: A REVIEW LITERATURE INTEGRATIVE (CIPEEX, 2022)
CELIAC DISEASE IS AN AUTOIMMUNE DISEASE CAUSED BY INTOLERANCE TO GLUTEN, A PROTEIN FOUND IN WHEAT, OATS, BARLEY, RYE AND THEIR DERIVATIVES, CAUSING VILLOUS ATROPHY OF THE INTESTINAL MUCOSA. THE DIAGNOSIS OF CELIAC DISEASE IS BASED ON A COMBINATION OF FINDINGS FROM THE PATIENT'S CLINICAL HISTORY AND SPECIFIC TESTS. PSYCHIATRIC DISORDERS HAVE BEEN FREQUENTLY REPORTED IN PATIENTS WITH CELIAC DISEASE, BEING ASSOCIATED WITH A WIDE SPECTRUM OF DISORDERS, INCLUDING ANXIETY DISORDERS, DEPRESSION, MIGRAINE, BIPOLAR, SCHIZOPHRENIA, EATING DISORDERS, AUTISM SPECTRUM DISORDERS, ATTENTION DEFICIT AND HYPERACTIVITY DISORDERS. THEREFORE, THIS WORK AIMED TO ANALYZE THE NEUROPSYCHOLOGICAL REPERCUSSIONS OF CELIAC DISEASE IN CHILDREN, ANALYZING THE MAIN DISORDERS TRIGGERED BY A GLUTEN-FREE DIET IN PEDIATRIC PATIENTS AND HOW THIS DISEASE INFLUENCES THE LIFESTYLE OF INFANTS. THEREFORE, IT IS CONCLUDED THAT CELIAC DISEASE IMPAIRS THE QUALITY OF LIFE, IN A WAY THAT REDUCES FUNCTIONALITY IN SOCIAL RELATIONSHIPS, IN EMOTIONAL LIFE AND PHYSICAL HEALTH, OBSERVING THE PREVALENCE OF PSYCHIATRIC DIAGNOSES PRESENT IN AT LEAST HALF OF THE CASES ANALYZED FOR THE PRESENT STUDY. THEN, THE INCREASE OF THE RATE OF EMOTIONAL AND BEHAVIORAL PROBLEMS IN CHILDREN AND ADOLESCENTS WITH CELIAC DISEASE EMPHASIZES THE IMPORTANCE OF EARLY DETECTION OF MENTAL HEALTH PROBLEMS IN THESE CHILDREN. IN ORDER TO FULFILL THE OBJECTIVES RAISED AND ANSWER THE RESEARCH DILEMMA, AN INTEGRATIVE LITERATURE REVIEW WAS USED AS A TOOL, WHICH WAS SUPPORTED BY INFORMATION TAKEN FROM THE VIRTUAL HEALTH LIBRARY (VHL), PUBMED, SCIENTIFIC ELECTRONIC DATABASES LIBRARY ONLINE (SCIELO) AND GOOGLE SCHOLAR.
Keywords: doença celíaca; infÃ¢ncia; dieta livre de glúten; distúrbios psiquiátricos